Food and western disease : health and nutrition from an evolutionary perspective - Lindeberg, Staffan , 1950- (Wiley-Blackwell, 2010)
"By looking at what we know of human evolution and disease in relation to the diets that humans enjoy now and prehistorically, the book allows the reader to begin to truly understand the link between diet and disease in the Western world and move towards a greater knowledge of what can be defined as the optimal human diet." "This book will be of great interest to nutritionists, dietitians and other members of the health professions. Evolutionary biologists and anthropologists will also find much of interest within the book. All university and research establishments where nutritional sciences, medicine, food science and biological sciences are studied and taught should have copies of this title."--BOOK JACKET.